2022
DOI: 10.1007/s00213-022-06178-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, open-label, cross-over clinical study to evaluate the pharmacokinetic, pharmacodynamic and safety and tolerability profiles of tobacco-free oral nicotine pouches relative to cigarettes

Abstract: Rationale Tobacco harm reduction (THR) involves encouraging adult smokers who would otherwise continue to smoke to transition to less harmful forms of nicotine delivery. These products must offer adult smokers reduced exposure to chemicals associated with tobacco combustion, satisfactory blood plasma nicotine levels and serve as an acceptable alternative. The most recent THR innovation is tobacco-free oral nicotine pouches. Objectives This study aimed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
1
23
0
4
Order By: Relevance
“…Te study confrms pharmacokinetics profle of ONPs is mainly oral mucosal absorption and not via swallowing/G.I. absorption [7]. Te time of maximum nicotine concentration observed (T max ) for the pouches products ranges from 22-26 minutes to 60 minutes [7,22].…”
Section: Onps Usage and Nicotine Absorptionmentioning
confidence: 94%
See 2 more Smart Citations
“…Te study confrms pharmacokinetics profle of ONPs is mainly oral mucosal absorption and not via swallowing/G.I. absorption [7]. Te time of maximum nicotine concentration observed (T max ) for the pouches products ranges from 22-26 minutes to 60 minutes [7,22].…”
Section: Onps Usage and Nicotine Absorptionmentioning
confidence: 94%
“…ONPs are composed of a permeable pouch and a nontobacco substrate to which nicotine and favors are added [6,7]. Te outer pouch material comprises viscose fbers bound together by chemical, heat, or solvent treatment.…”
Section: Major Constituents and Categories Of Onpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the additional approaches of the ONPs, studies also report the impact of ONPs on lung as case studies put forward that pulmonary aspirations of smokeless tobacco products activate recurrent pulmonary infiltrations and multifocal airway obstructions in the lungs of the users probably causing aspiration pneumonia [44]. Recent evidence investigated the pharmacokinetic parameters of ONPs and reported that oral nicotine pouches carry the potential to be an acceptable substitute for adult smokers as the users can achieve adequate nicotine levels to deliver into the body [45]. Our recent in vitro investigation focused on oral-pulmonary health effects of Snus and ONPs indicating that the flavored ONPs are risky and likely to cause local and systematic toxicological responses during chronic consumption [27].…”
Section: Application Of Onps In Research Studiesmentioning
confidence: 99%
“…Despite the significant increases in the usage of ONPs in the U.S., limited studies have been conducted so far that have delved into understanding the health effects of ONP usage [4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%